Visible and infrared dual-band imaging via Ge/MoS2van der Waals heterostructure - Hwang, Aujin; Park, Minseong; Park, Youngseo; Shim, Yeongseok; Youn, Sukhyeong; Lee, Chan Ho; Jeong, Han Beom; Jeong, Hu Young; Chang, Jiwon; Lee, Kyusang; Yoo, Geonwook; Heo, Junseok (Science Advances, 2021)
Multispectral photodetectors are emerging devices capable of detecting photons in multiple wavelength ranges, such as visible (VIS), near infrared (NIR), etc. Image data acquired with these photodetectors can be used for effective object identification and navigations owing to additional information beyond human vision, including thermal image and night vision. However, these capabilities are hindered by the structural complexity arising from the integration of multiple heterojunctions and selective absorbers. In this paper, we demonstrate a Ge/MoS2 van der Waals heterojunction photodetector for VIS- and IR-selective detection capability under near-photovoltaic and photoconductive modes. The simplified single-polarity bias operation using single pixel could considerably reduce structural complexity and minimize peripheral circuitry for multispectral selective detection. The proposed multispectral photodetector provides a potential pathway for the integration of VIS/NIR vision for application in self-driving, surveillance, computer vision, and biomedical imaging.
Keywords: Image data; Infrared dual bands; Multi-spectral; Multiple wavelengths; Object identification; Selective detection; Structural complexity; Van der Waal; Visible near-infrared; Wavelength ranges